Kinerja Bidan dalam Memberikan Pelayanan Antenatal Care: Suatu Kajian Pustaka: Performance of Midwives in Providing Antenatal Care Services: A Review - Bella Octaviani Violinansa; Chriswardani Suryawati; Rani Tyas Budiyanti (Jurnal Sains dan Kesehatan, 2021)
Abstract In 2017, 106 Primary Health Care in Indonesia performed the Antenatal Care (ANC) component properly and correctly according to the 9T, 7T, 5T standards, respectively 18.8%, 23.2%, and 31.7%. Only 20.4% of the Primary Health Care had all the equipment, medicines, and media supporting 9T of ANC. Only one fifth of the midwives provided ANC services according to standards. This study to analyze the performance of midwives in providing Antenatal Care services and the factors that influence it seen from the studies that have been done. This study uses literature review method by analyzing 20 indexed journals, both national and international journals in the last 5 years. Review method with a systematic approach. The result are total of 13 journals stated that the performance of midwives in Antenatal Care services is good (>50%). 5 of 6 journals stated that there is a relationship between performance and age. 5 of 5 journals stated that there is a relationship between performance and facilities. 4 of 6 journals stated that there was a relationship between performance and training. 4 out of 4 journals stated that there is a relationship between performance and tenure. 10 out of 12 journals stated that there is a relationship between knowledge and performance. 8 of 11 journals stated that there is a relationship between motivation and performance. 3 of 5 journals stated that there is a relationship between leadership and performance. 3 out of 4 journals stated that there is a relationship between workload and midwife performance.The conclusion is the midwife's performance is good. Factors that influence performance are age, infrastructure, training, tenure, knowledge, motivation, leadership, and workload. The factor most researched is knowledge. The most influential factors are infrastructure and years of service. Abstrak Tahun 2017 sebanyak 106 puskesmas di Indonesia yang melakukan komponen Antenatal Care (ANC) secara baik dan benar menurut standar 9T, 7T, 5T berturut-turut sebesar 18,8%, 23,2%, dan 31,7%. Puskesmas yang memiliki seluruh peralatan, obat, dan media penunjang ANC 9T hanya sebesar 20,4% saja. Bidan yang melakukan pelayanan ANC sesuai standar hanya seperlimanya saja. Tujuan penelitian ini untuj menganalisis kinerja bidan dalam memberikan pelayanan Antenatal Care dan faktor-faktor yang mempengaruhi dilihat dari penelitian-penelitian yang telah dilakukan. Penelitian ini menggunakan metode literature review dengan menganalisis 20 jurnal terindeks, baik jurnal nasional maupun internasional dalam kurun waktu 5 tahun terakhir. Metode review dengan pendekatan sistematis. Sebanyak 13 jurnal menyatakan kinerja bidan dalam pelayanan Antenatal Care sudah baik (>50%). 5 dari 6 jurnal menyatakan terdapat hubungan antara kinerja dengan usia. 5 dari 5 jurnal menyatakan terdapat hubungan antara kinerja dengan sarana prasana. 4 dari 6 jurnal menyatakan terdapat hubungan antara kinerja dengan pelatihan. 4 dari 4 jurnal menyatakan terdapat hubungan antara kinerja dengan masa kerja. 10 dari 12 jurnal menyatakan terdapat hubungan antara pengetahuan dengan kinerja. 8 dari 11 jurnal menyatakan terdapat hubungan antara motivasi dengan kinerja. 3 dari 5 jurnal menyatakan terdapat hubungan antara kepemimpinan dengan kinerja. 3 dari 4 jurnal menyatakan terdapat hubungan antara beban kerja dengan kinerja bidan. Dapat disimpulkan kinerja bidan sudah baik. Faktor yang mempengaruhi kinerja yaitu usia, sarana prasarana, pelatihan, masa kerja, pengetahuan, motivasi, kepemimpinan, dan beban kerja. Faktor yang paling banyak diteliti yaitu pengetahuan. Faktor yang paling berpengaruh yaitu sarana prasarana dan masa kerja.